ANALISA KEKARASAN MATERIAL BAJA ST 37 AKIBAT PENGARUH PENGELASAN OXY ACETYLENE - Syafrizal Syafrizal; Ade Irvan Tauvan (Jurnal Elektra, 2019)
Testing the hardness of ST 37 plate material was carried out to determine the effect of welding on changes in the hardness of plate material. Hardness testing is carried out in two stages, namely before welding, the plate material has been tested with rockwell harness scale B, which is 100 kgf (as initial testing), then hardness testing is done again after welding with Oxy- Acetylene welding at pressure 1.5 kg/cm2 of Oxy gas and 0.2 kg/cm2 of Acetylene gas. Hardness testing was carried out on two sides, first in the Heat-Affected Zone (HAZ) area, then in the weld seam area. Plate welding process with welding is by melting the main plate and at the same time as a connecting material (without additional material). From the results of testing before and after welding there is a phenomenon, where the Heat-Affected Zone (HAZ) area increases the hardness of the material, but in the weld joint area (Las seam) it is the opposite. In the HAZ area there was an increase in violence of about 5.3%, but in the weld area (Las Las) there was a decrease in violence reaching 38%.